Spleen as a Site for Hematopoiesis of a Distinct Antigen Presenting Cell Type - Helen C. O'Neill; Kristin L. Griffiths; Pravin Periasamy; Rebecca A. Hinton; Ying-Ying Hey; Sawang Petvises; Jonathan K. H. Tan (Hindawi Limited, 2011)
While spleen and other secondary tissue sites contribute to hematopoiesis, the nature of cells produced and the environment under which this happens are not fully defined. Evidence is reviewed here for hematopoiesis occurring in the spleen microenvironment leading to the production of tissue-specific antigen presenting cells. The novel dendritic-like cell identified in spleen is phenotypically and functionally distinct from other described antigen presenting cells. In order to identify these cells as distinct, it has been necessary to show that their lineage origin and progenitors differ from that of other known dendritic and myeloid cell types. The spleen therefore represents a distinct microenvironment for hematopoiesis of a novel myeloid cell arising from self-renewing hematopoietic stem cells (HSC) or progenitors endogenous to spleen.